Setting on demand for digital concrete – Principles, measurements, chemistry, validation. (June 2020) - Reiter, Lex; Wangler, Timothy; Anton, Ana; Flatt, Robert J.
Abstract: Digital fabrication with concrete is a field of rapidly developing building processes – including layered extrusion - where specific yield stress evolution over time is needed, owing to concrete loading during fabrication. By combining physico-chemical principles of concrete yield stress evolution with strength requirements imposed by the building process an avenue is devised for an effective development of these processes. Most notably, strength should grow linearly with time to ensure strength-based self-support, while it should growth with its third power to avoid self-weight induced buckling. It is argued that the needed evolution can be achieved by adequately controlling cement hydration during fabrication. Specifically, we outline the Set on Demand approach, relying on a combination of admixtures adequate for the process under study. This strategy is implemented with newly developed methods capable of measuring concrete yield stress evolution at rest, thus providing the link from chemistry to processing and mechanical stability.